Perubahan Kurikulum di Madrasah Aliyah Negeri 2 Ponorogo Sebagai Upaya Peningkatan Kualitas Lembaga Pendidikan Islam - Ahmadi Ahmadi; Yayah Chairiyah; Safiruddin Al Baqi (IAIN Ponorogo, 2021)
AbstractQuality education today is an essential necessity in human life. The purposes of this research are to describe how the dynamics of curriculum goes on. It used a qualitative descriptive approach. The instruments of collecting data are observation, interview, and document. The data must be analyzed by the following cycles: reduction, display and verification. It showed that; curriculum religious teacher training is different with the curriculum of Islamic High School. The implementation of the curriculum has to improve some knowledge and policy continuously, especially, to master the curriculum component system supported to the vision. Those are; setting up teachers and education staffs with the standards of educational, structuring teachers to teach according to their field of study, and involving them in any kinds of training and curriculum development policy. It faces several obstacles lacking of curriculum development experiences and theories, educational personnel should contribute more than before in curriculum development.Key words; Curriculum, education system, Islamic education, madrasah. AbstrakPendidikan yang berkualitas merupakan keperluan esensi yang amat penting dalam kehidupan manusia masa sekarang. Penelitian ini bertujuan untuk mengkonstruk bagaimana dinamika kurikulum berlangsung. Penelitian menggunakan pendekatan studi kasus. Gambaran fakta data diperoleh melalui teknik pengamatan, wawancara, dan dokumen. Data dianalisa dengan siklus; reduksi, pemaparan dan simpulan. Hasil riset menunjukan; kurikulum Pendidikan Guru Agama berbeda dengan Madrasah Aliyah, implementasi kurikulum madrasah meningkatkan pengetahuan dan komponen kurikulum yang mendukung terhadap visi. Proses tahapan tersebut; menyiapkan guru dan staff perkantoran yang sesuai dengan kualifikasi pendidikan, guru mengajar sesuai dengan bidangnya, mengikutsertakan mereka dalam kebijakan program pelatihan dan pengembangan kurikulum. Implementasi menghadapi beberapa kendala; kurang pengalaman dalam pengembangan dan pengasaan teori, pelaksana kurikulum seharusnya dapat berkonstribusi lebih dalam pengembangannya.